Rola menedżerów w procesach gospodarczych organizacji - Czekaj, Janusz; Jabłoński, Marek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The paper is focused on pointing out the leading role of managers in organizational processes. In that respect, the article presents the key role of managers in organizational development, especially in the light of the resource-based view of the firm, E. Penrose's growth theory and systemic approach to competences within organization. On that basis there has been presented the crucial impact of managers on strategic and business processes within organization. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 95-104